Pasantía auditoria financiera a la Personería Municipal de Armenia para la vigencia 2012 (2013)
The to the Personería Municipal de Armenia validity 2012, was establish according to the procedures established for the development phase of the audit process in accordance with the Territorial Audit Guide (TAG) emitted by the Comptroller General of the Republic. In the planning phase were analyzed financial statements and budget execution, allowing to identify the most relevant accounts and then to evaluate them. In this evaluation were verified implicit claims in the financial statements and found some situations where information did not meet the characteristics that must hold. Subsequently, with the implementation phase it was found that information was according to regulations, giving as a result the conformation of five observations, in which five were administrative incidence. Finally, we proceeded with the development of inform’ phase in which was giving an opinion where was concluded that the financial statements of the Personeria Municipal de Armenia validity 2012, present fairly the organization's financial information, generating an unqualified opinion by the audit team.